Histomorphometry of umbilical vessels of intrauterine growth restricted neonates - Kotrannavar, Sangeeta S.; Shirol, Veereshkumar S.; Dhumale, Hema A.; Humbarwadi, Rajendra S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: A complex and coordinated interaction between maternal, placental and fetal factors influences the normal fetal growth. Any disruption in this complex system can lead to intrauterine growth restriction (IUGR).The main objective of the study is to evaluate histomorphometric differences in umbilical vessels of appropriate for gestational age (AGA) and intrauterine growth restricted (IUGR) neonates and to observe histomorphometric differences existing in umbilical vessels between male and female sex. Methods: A prospective observational study included 110 umbilical cords (UC) procured from KLES Dr. Prabhakar Kore Charitable Hospital and Medical Research Centre, Belagavi, India. Formalin fixed, paraffin embedded tissues were processed and stained with hematoxylin and eosin, and Masson’s trichrome stain. Histomorphometric measurements of cross sectional areas (CSA) of umbilical vessels like total vessel area (mm2), lumen area (mm2) and vessel wall area (mm2) were taken with 40X magnification with the help of Olympus microscope having digital image analyzer attachment. The relevant personal data of mother and neonate were recorded. Independent t test was used to compare means and chi-square test for categorical variables. Results: Umbilical vessels of IUGR neonates had significantly reduced total vessel area, vessel wall area and lumen area compared to AGA neonates (except lumen area of umbilical arteries). Ratios of total vessel area to lumen area and vessel wall area to lumen area were significantly increased in human umbilical vein (HUV) of IUGR neonates. No significant difference in CSAs of umbilical vessels was observed between male and female sex in both groups. Conclusions: IUGR is associated with significant structural changes in umbilical vessels of full term neonates. These changes are more obvious in HUV than human umbilical artery (HUA). It can be detected prenatally and used as an indicator of impending IUGR.